SISTEM PENGOLAHAN PERSEDIAAN SEAFOOD PADA PT. JAYA ANUGRAH SUKSES ABADI MEDAN MENGGUNAKAN VISUAL BASIC.NET - Nofyta Andryani; Jovi Antares; Afni Nia Sari (Universitas Dharmawangsa, 2021)
system to provide facilities for operational in industries .The study is done in pt .Jaya perennial gift success .Methods used is quantitative methods. The data was undertaken during his field of documentation, collected data , interview observation and review library concerned with theories.